“Suicide: Yay or Nay?” X Autobase Account as Safe Space for College Students - Uswatul Chabibah (Profetik: Jurnal Komunikasi, 2024)
Suicide incidents among college students have been increasing in the last decade before the turn of millennium. Since the young people are active users of social media, this research aims to map the topics of the college students’ post to X (formerly Twitter) autobase account using content warnings (“TW”, “trigger warning” and “CW”, “Content Warning”) to study sensitive or disturbing contents that may triggers trauma. Many college students in Indonesia created campus-based autobase accounts as a platform for sharing information both academic and non-academic, expressing opinions and feelings, socializing, etc. Its anonymous feature plays as a safe space so the users can be themselves on this platform, including posting sensitive contents. This research looked at autobase X accounts of three campuses in Indonesia. They are Institut Teknologi Bandung, Universitas Diponegoro, Semarang, and Universitas Gadjah Mada, Yogyakarta. This research is a netnographic research by collecting tweets containing trigger warnings from the autobase accounts of the three campuses, then grouping the tweets into topics. Using literature review related to the concepts of anonymity and safe space, it is found that autobase accounts with their anonymous feature is a platform with potential to be a safe space for college students to seek help, including helps for suicidal thoughts, mental health and self harm, sexual harassment, and express things that are considered taboo, especially in Indonesian culture, such as LGBTQ+ issues. This is also an effort to acknowledge collective vulnerability among students that may need further intervention